The Use of Porpe (Predict, Organize, Rehearse, Practice, Evaluate) Strategy in Teaching Reading Comprehension - Asrikandi, Pajriah (Universitas Hamzanwadi, 2017)
This study aimed at examining the effectiveness of PORPE (predict, organize, rehearse, practice, evaluate) strategy in teaching reading comperhension.This research was designed as a pre-experimental research. The sample of this reserach was students of the tenth graders of Language 2 of MA Muallimin NW Pancor. In collecting the data, a pre-test and a post-test were given to students of the tenth graders of MA Muallimin NW Pancor in the school year 2015-2016. Descriptive statistic and paired simple t test were used to analyze the data by using SPSS 17.0 for windows. Based on the result of descriptive statistic, the mean score of post-test (20.59 ) was higher than pre-test (13.19). After submitting the data to a paired samples t-test, the present researcher found that there was a significant difference in the mean scores between the pre-test and the post-test, t(df=26) = 21.18 < p = 0.01, meaning that the alternative hypothesis was accepted. PORPE strategy is significantly effective in teaching reading comprehension of narrative texts for the tenth graders of MA Muallimin NW Pancor in the school year 2015-2016. Considering the process and the results of this research, the present researcher suggests that the English teacher should use PORPE strategy.